Next-generation sequencing (NGS) profiling of matched tumor and circulating tumor DNA (ctDNA) in head and neck squamous cell carcinoma (HNSCC). (April 2023) - Economopoulou, Panagiota; Spathis, Aris; Kotsantis, Ioannis; Maratou, Eirini; Anastasiou, Maria; Moutafi, Myrto K.; Kirkasiadou, Maria; Pantazopoulos, Anastasios; Giannakakou, Maria; Edelstein, Daniel L.; Sloane, Hillary; Fredebohm, Johannes; et al.
Highlights: In a cohort of patients with head and neck cancer, concordance of genotyping results between tumor DNA and ctDNA was 53.3%. TP53 mutations were most commonly identified at baseline in both ctDNA (32.6%) and tumor DNA (40%). The presence of mutations in tissue or plasma samples at baseline was associated with decreased overall survival. Abstract: Objectives: The aim of this pilot study was to evaluate the presence of somatic mutations in matched tumor and circulating DNA (ctDNA) samples from patients with primary head and neck squamous cell carcinoma (HNSCC) and assess the association of changes in ctDNA levels with survival. Materials and methods: Our study included 62 patients with stage I-IVB HNSCC treated with surgery or radical chemoradiotherapy with curative intent. Plasma samples were obtained at baseline, at the end of treatment (EOT), and at disease progression. Tumor DNA was extracted from plasma (ctDNA) and tumor tissue (tDNA). The Safe Sequencing System was used assess the presence of pathogenic variants in four genes (TP53, CDKN2A, HRAS and PI3KCA) in both ctDNA and tDNA. Results: Forty-five patients had available tissue and plasma samples. Concordance of genotyping results between tDNA and ctDNA at baseline was 53.3%. TP53 mutations were most commonly identified at baseline in both ctDNA (32.6%) and tDNA (40%). The presence of mutations in this restricted set of 4 genes in tissue samples at baseline was associated with decreased overall survival (OS) [median 58.3 months for patients with mutations vs. 89 months for patients without mutations, p < 0.013]. Similarly, patients presenting with mutations in ctDNA had shorter OS [median 53.8 vs. 78.6 months, p < 0.037]. CtDNA clearance at EOT did not show any association with PFS or OS. Conclusions: Liquid biopsy enables real-time molecular characterization of HNSCC and might predict survival. Larger studies are needed to validate the utility of ctDNA as a biomarker in HNSCC.